Design and investigation on a piezoelectric screw pump with high flowrate. (28th June 2021) - Pan, Qiaosheng; Li, Yinghao; Wang, Xiaoliang; Jiang, Haiyang; Wang, Quan; Huang, Ziliang; Zhang, Yong
Abstract: A novel piezoelectric screw pump is proposed in this study to improve the output flowrate of piezoelectric valveless pump. Piezoelectric screw pump is composed of a piezoelectric driving system and a screw pump body, which could realize the separation of driving and pump body. The driving system consists of two groups of piezoelectric vibrators and a ring hinge. The piezoelectric vibrators are made of four displacement amplifiers and four piezoelectric stacks. The screw pump body consists of an outer cylinder, a threaded pipe and a screw. The threaded pipe and screw are designed with rectangular threads. A certain clearance exists on their matching surface as the liquid flow channel. The screw pump body is made by 3D printing. This paper introduces the operating principle of the piezoelectric screw pump, and analyzes the factors influencing the output performance by finite element simulation. Four groups of piezoelectric screw pump prototypes with different parameters are made. The simulation results are verified by experiments. The experimental results show that under the driving voltage of 600 V pp, the maximum back pressure of the prototypes is 5.3 kPa, and the maximum flowrate is 71.4 ml min −1 .